# Error solving differential equations: Infinite expression encountered?

Posted 14 days ago
151 Views
|
|
0 Total Likes
|
 Hi GuysPlease refer to the below code. The system being presented two elastic pendulums connected by a rigid rod. I have represented the system using Lagrangian mechanics with a holonomic constraint to develop the required behavior.I have used the holonomic constraint to represent a variable as a function of other variables. The time derivative is also required, thus all the equations which are presented in the beginning.The (b+r) term presented as "B" is made the subject of the formula and then the derivative also taken. When I run the code I am attaining an error with regards to a non-numerical value of a derivative being 0. Can anyone assist with regards to what my problem is? Further to this I would appreciate any advice with regards to issues with the manner in which I have coded? I come from a Matlab and Python mindset. r = 1; L = 2; m1 = 3500; m2 = 3500; k = 353160; A = a'[t] + r; R1 = 2*A*Cos[theta1[t]]*Cos[theta2[t]]; one = -A^2 + L^2; two = A^2*Cos[2*theta1[t] - 2*theta2[t]]; three = -L^2*Cos[2*theta2[t]]; four = -2*A*L*Sin[theta1[t]]; five = -2*A*L*Sin[theta1[t] - 2*theta2[t]]; R2 = Sqrt*Sqrt[one + two + three + four + five]; six = 2*L*Sin[theta2[t]]; seven = 2*A*Sin[theta1[t]]*Sin[theta2[t]]; R3 = six + seven; B = R1 + R2 + R3; R1dot = 2*a'[t]*Cos[theta1[t]]*Cos[theta2[t]] - 2*A*theta1'[t]*Sin[theta1[t]]*Cos[theta2[t]] - 2*A*theta2'[t]*Cos[theta1[t]]*Sin[theta2[t]]; oned = -2*a'[t]*A; twod = 2*a'[t]*A*Cos[2*theta1[t]]*Cos[2*theta2[t]] - A^2*2*theta1'[t]*Sin[2*theta1[t]]*Cos[2*theta2[t]] - A^2*Cos[2*theta2[t]]*2*theta2'[t]*Sin[2*theta2[t]] + 2*a'[t]*A*Sin[2*theta1[t]]*Sin[2*theta2[t]] + A^2*2*theta1'[t]*Cos[2*theta1[t]]*Sin[2*theta2[t]] + A^2*Sin[2*theta1[t]]*2*theta2'[t]*Cos[2*theta2[t]]; threed = L^2*s*theta2'[t]*Sin[2*theta2[t]]; fourd = -2*a'[t]*L*Sin[theta1[t]] - 2*A*L*theta1'[t]*Cos[theta1[t]]; fived = -2*a'[t]*L*Sin[theta1[t]]*Cos[2*theta2[t]] - 2*A*L*theta1'[t]*Cos[theta1[t]]*Cos[2*theta2[t]] - 2*A*L*Sin[theta1[t]]*2*theta1'[t]*Sin[2*theta2[t]] + 2 a'[t]*L*Cos[theta1[t]]*Sin[2*theta2[t]] - 2*A*L*theta1'[t]*Sin[theta1[t]]*Sin[2*theta2[t]] + 2*A*L*Cos[theta1[t]]*2*theta2'[t]*Cos[2*theta2[t]]; sixd = 2*L*theta2'[t]*Cos[theta2[t]]; sevend = 2*(a'[t]*Sin[theta1[t]]*Sin[theta2[t]] + A*theta1'[t]*Cos[theta1[t]]*Sin[theta2[t]] + A*Sin[theta1[t]]*theta2'[t]*Cos[theta2[t]]); R2dot = (oned + twod + threed + fourd + fived)/(2* Sqrt[one + two + three + four + five]); R3dot = sixd + sevend; bdot = (0.5*R1dot + R2dot + R3dot)/(4*Sqrt[R1 + R2 + R3]); NDSolve[{b''[ t] == (m2*theta2'[t]^2*B - k*(B - r) + 9.81*m2*Cos[theta2[t]])/ m2, a''[t] == (m1*theta1'[t]^2*A - k*a[t] + 9.81*m1*Cos[theta1[t]])/m2, theta1''[t] == (-2*m1*theta1'[t]*a'[t]*A - 9.81*m1*Sin[theta1[t]]*A)/(m1*A^2), theta2''[t] == (-2*m2*theta2'[t]*bdot*B - 9.81*m2*Sin[theta2[t]]*B)/(m2*B^2), a == 0, a' == 0, b == 0, b' == 0, theta1 == 0, theta1' == 0, theta2 == 0, theta2' == 0}, {a, b, theta1, theta2}, {t, 0, 10}] Answer
 It seems to me that your equation for theta2''[t] is singular when t=0 and theta1 == theta2 == 0. Answer